Developing multiliteracy in children at TBM Smart Friends through flip read-aloud and bookish play applications - Oktha Ika Rahmawati; Chyntia Heru Woro Prastiwi; Fifi Zuhriah; Norita Prasetya Wardhani; Ludfi Anggraeni; Febrika Dilla Saputri (Universitas Muhammadiyah Magelang, 2024)
The diverse literacy activities are one of the attractions for visitors to a community reading park. The lack of variety of activities at the Smart Friends Community Reading Park (CRP) is one of the reasons why this CRP is no longer visited by children in the surrounding area. Therefore, this community service activity aims to build multiliteracy of children around the CRP by holding flip read-aloud and bookish play activities. The method used in this activity is the direct learning method. This program has succeeded in reviving the reading park which can actually provide many benefits for children in building multiliteracy. In it, children learn to listen, retell, make decisions, train creativity and imagination.